2011
DOI: 10.1002/mus.22004
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical study of the infrapatellar branch of the saphenous nerve using ultrasonography

Abstract: The infrapatellar branch of the saphenous nerve can be depicted by ultrasonography. Precise mapping of its anatomical course may have significant clinical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
67
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 14 publications
(57 reference statements)
6
67
1
1
Order By: Relevance
“…As an example, the infrapatellar branch of the saphenous nerve (IPBSN) is solely a sensory nerve that innervates the anterior and inferior parts of the knee capsule as well as the skin over the antero-medial knee [52][53][54][55][56]. Several studies (including two randomized, double-blinded, placebo-controlled trials) have examined the efficacy of a selective nerve block of the IPBSN for treatment of postoperative knee pain [57][58][59][60][61].…”
Section: Perioperative Treatment For Post-surgical Painmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, the infrapatellar branch of the saphenous nerve (IPBSN) is solely a sensory nerve that innervates the anterior and inferior parts of the knee capsule as well as the skin over the antero-medial knee [52][53][54][55][56]. Several studies (including two randomized, double-blinded, placebo-controlled trials) have examined the efficacy of a selective nerve block of the IPBSN for treatment of postoperative knee pain [57][58][59][60][61].…”
Section: Perioperative Treatment For Post-surgical Painmentioning
confidence: 99%
“…In this study, the IPBSN was located using anatomical landmarks [54]. Subsequently, a method for locating the anterior femoral cutaneous nerve (AFCN), which innervates the anterior superior part of the knee capsule and may offer additional postoperative relief, was defined and validated in a cadaveric model [64].…”
Section: Perioperative Treatment For Post-surgical Painmentioning
confidence: 99%
“…Finding consistency within IPBSN branching has been the aim of many studies since. 2,9,14,16,18,34 Despite our relatively small sample size of 10 cadaveric knees, the relationship between the IPBSN and bony landmarks was no different than those reported in the large seminal study by Mochida and Kikuchi. 24 In their study of 129 knees, these authors reported an insignificant difference in the mean distance from the IPBSN to the midpatella in left (52.2 mm) and right (54.2 mm) knees.…”
Section: Discussionmentioning
confidence: 54%
“…4 Ultrasound with or without Doppler can be used to preidentify the nerve. 2,18 We personally recommend a superficial-only skin incision and the use of a blunt-tipped trocar. Additionally, structures such as the superior medial and lateral genicular arteries and the medial patellofemoral ligament occur at the region under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the nerve can be difficult to visualize in the medial aspect of the knee [2,3]. We currently identify and mark the maximum point of tenderness along the course of the infrapatellar nerve and scan for the nerve between the fascial planes.…”
mentioning
confidence: 99%